Intoxication by pesticides in Parana North Central Mesoregion – 2007 to 2011 - Dias Mangolini Neves, Pedro; Bellini, Marcella (O Mundo da Saúde, 2012)
This research is based on epidemiological records of toxicological occurrences and individual records of toxicological investigation of pesticide poisoning in the Poison Control Center of Regional University Hospital of Maringá. Intoxication in patients assisted during the years 2007 to 2011, from municipalities belonging to the Parana North Central Mesoregion where Maringá is located. As a result, we can establish that approximately 70% of males were intoxicated, and the age groups most affected are 20-29 years and 30-39 years. Suicide attempts appear as the main motivation of hospitalization (possibly disguising chronic intoxication), and the major factors involved in the poisonings are insecticides, with 60%, and herbicides, with 25%. We identified the need for public health policies for promoting the immediate decrease of this situation, for these poisonings are noticeable, and there are no records of food poisoning.